Characteristics of boundary layer turbulence energy budget in Shenzhen area based on coherent wind lidar observations - J. Xian; J. Xian; Z. Qiu; H. Rao; Z. Cheng; X. Lin; C. Lu; H. Yang; N. Zhang; N. Zhang (Atmospheric Chemistry and Physics)
Due to the limitations of observations with meteorological towers and aircraft, there is a lack of research on the vertical characteristics of the atmospheric boundary layer in relation to the budget terms of turbulence kinetic energy (TKE). This study reveals the seasonal characteristics of the TKE budget and processes in Shenzhen using long-term observational data from coherent wind lidar. We found that the TKE variations in the region transition in behavior around 14:00 local time (LT), mainly because of changes in buoyancy generation. We determined that TKE is strongest in summer and has the highest impact at high altitudes in autumn in Shenzhen. Our results indicate that above 360 m, the daytime turbulent transport term in all seasons is positive, contributing up to 20 % of the total TKE budget, and the dissipation rate term is the only factor that dominates energy dissipation. We also found seasonal differences in the vertical characteristics of the dissipation rate in the region, with maximum values observed near the ground during spring, summer, and autumn. Our results indicate that near the ground, buoyancy is the main generation process of TKE, contributing up to 60 % of the total budget. Above 570 m, the role of shear generation gradually becomes more prominent, comparable to buoyancy generation. These findings not only enrich our understanding of the vertical structure of atmospheric turbulence but also provide new observational data and theoretical support for the parameterization of the turbulence energy budget in climate models, which can help improve atmospheric predictions.